Ichthyosis Linearis Circumflexa - Gharami R. C (Wolters Kluwer Medknow Publications, 2001)
A 4 year old female child presented with ichthyosiform erythroderma. She had few serpiginous ichthyotic patches on her face. The case is presented for its rarity.